Developing a mobile epilepsy management application integrated with an electronic health record for effective seizure management. (February 2020) - Yoo, Sooyoung; Lim, Kahyun; Baek, Hyunyoung; Jang, Sae-Kyun; Hwang, Ga-young; Kim, Hunmin; Hwang, Hee
Highlights: The study developed and evaluated an mHealth service for managing epilepsy compatible with the hospital's EHR system. Functions such as seizure Diary, Medication, Appointments, Survey were developed to aid patients' epilepsy management. The usability test showed participants were highly satisfied with the service despite differences between task success rate. The degree of perceived importance of the functions differed by participants' characteristics. Abstract: Introduction: Epilepsy is a chronic neurological disorder characterized by recurrent spontaneous seizures. Over 70% epilepsy patients can live normally if their seizures can be controlled. For this, many factors should be tracked and managed, but doing so is hard because of individual differences. There are mobile applications to help track these factors; however, no application covers crucial factors comprehensively, and they are complicated to use. Therefore, this study aimed to develop a mobile epilepsy management application covering crucial factors comprehensively in a user-friendly way. We evaluated the pilot version with a usability and satisfaction survey and an interview. Methods: We established a task force comprising professionals from various fields who participated in all processes of this research. Existing service analysis and professional interviews were conducted to draw a function list. User interface and graphic user interface were designed under the supervision of the task force. After developing the application's pilot version, usability and satisfaction of the application were evaluated with eight patients and caregivers through scenario-based usability test, satisfaction survey, and interview. Results: All existing mobile epilepsy management applications provide seizure and medication diary functions. We decided to provide six main functions: seizure diary, medication reminder, appointments, outpatient survey, education materials, and personal dashboard (My epilepsy). We also integrated the application with the hospital's electronic health record system. To simplify usability, frequently used and relatively important functions are located in the main page as "seizure recording" and "medication diary." Additionally, when designing graphics, art therapy was used to enhance psychological stability. For evaluation, eight participants were recruited. In scenario-based tasks, among 10 tasks, all participants completed six tasks. However, only 37.5% participants could record seizures in detail. System Usability Scale score was 84.5 points, indicating that the system was satisfactory. Conclusion: This study confirmed that patients' satisfaction of this application were high. Additionally, it helped them record their seizures accurately, which is very useful for seizure trend analysis, discovering seizure trigger factors, and ensuring efficient management of epilepsy. Through integration with the electronic health record, patient medical information could be utilized to guide physicians' decision-making for setting future medical treatment plan and could contribute greatly to the overall management of epilepsy.